An Adaptive Opportunistic Network Coding Mechanism in Wireless Multimedia Sensor Networks - Hang Shen; Guangwei Bai; Lu Zhao; Zhenmin Tang (International Journal of Distributed Sensor Networks)
The network coding technique is promising for improving the performance of video communication in wireless multimedia sensor networks. However, some special characteristics of existing wireless network coding mechanisms degrade the performance of video data delivery. This work begins with a thorough investigation and understanding of the performance limitations of existing wireless network coding mechanisms. On this basis, we propose an Adaptive Opportunistic Network Coding mechanism (AONC) to improve the transmission quality of video stream in wireless multimedia sensor networks. First, we propose a novel asymmetric coding method to process the video data of different lengths. The aim is to improve data exchange gain. Second, we design an opportunistic forwarding strategy based on dynamic priority to ensure that packets have a better chance to be coded and transmitted, thus achieving much higher throughput. Finally, we present a traffic-aware data scheduling algorithm, working together with the above network coding mechanism, to reduce the loss of potential coding opportunities. Our simulation results demonstrate that, compared with the existing typical network coding mechanisms, AONC can greatly enhance video transmission quality and efficiently utilize bandwidth and energy resources.